Primerjava dveh metod za ugotavljanje števila gnezdečih malih ponirkov Tachybaptus ruficollis, črnih lisk Fulica atra in zelenonogih tukalic Gallinula chloropus - Vogrin, Milan (Acrocephalus, 1999)
In the article a comparison of two different methods for estimating numbers ofpairs of the Little Grebe Tachybaptus ruficollis, Common Coot Fulica atra and Common Moorhen Gallinula chloropus during the breeding season is presented. According to the first method, individuals/pairs were counted during the breeding period and the number of breeding pairs estimated on the basis of the average number of the counted individuals. Both methods were applied at Vrbje pond in the Savinja valley and at Rače ponds (Dravsko polje) in 1998. All ponds were heavily overgrown (40-75%) with water vegetation. Numbers of the counted pairs per dates and localities and numbers of the foundnests at separate localities are presented in Tables 1 and 2. A comparison between the two methods has shown that during normal counting the number of the Little Grebe is underestimated by twice, and the number of the Common Moorhen by approx. 2.5 times. Numbers of the counted Common Coot dependmainly on the locality and the bird's migration dynamics. When Common Coots begin to gather at a certain locality already in the middle of the summer, they can be grossly overestimated (the case of Vrbje pond: Table 1). On the basis of the results and data from literature (DOMBROWSHI et al. 1993),the author suggests that on waters where vegetation covers approx. 50% of the surface, the number of the counted Little Grebe is multiplied by 2, andthe number of the Common Moorhen by 2.5. For more accurate results, however, nests must be found or the number of pairs checked by playbacks of the territorial calling of the species.
Keywords: Birds; ornitologija; bird; ptice; Ecosystem; gnezdenje; Population density; Nesting behavior